Leveraging an existing whole‐genome resequencing population data set to characterize toll‐like receptor gene diversity in a threatened bird. (14th June 2022) - Magid, Molly; Wold, Jana R.; Moraga, Roger; Cubrinovska, Ilina; Houston, Dave M.; Gartrell, Brett D.; Steeves, Tammy E.
Abstract: Species recovery programs are increasingly using genomic data to measure neutral genetic diversity and calculate metrics like relatedness. While these measures can inform conservation management, determining the mechanisms underlying inbreeding depression requires information about functional genes associated with adaptive or maladaptive traits. Toll‐like receptors (TLRs) are one family of functional genes, which play a crucial role in recognition of pathogens and activation of the immune system. Previously, these genes have been analysed using species‐specific primers and PCR. Here, we leverage an existing short‐read reference genome, whole‐genome resequencing population data set, and bioinformatic tools to characterize TLR gene diversity in captive and wild tchūriwat'/tūturuatu/shore plover ( Thinornis novaeseelandiae ), a threatened bird endemic to Aotearoa New Zealand. Our results show that TLR gene diversity in tchūriwat'/tūturuatu is low, and forms two distinct captive and wild genetic clusters. The bioinformatic approach presented here has broad applicability to other threatened species with existing genomic resources in Aotearoa New Zealand and beyond.